PENCEGAHAN TERSANGKA KE LUAR NEGERI OLEH KPK DALAM SISTEM PERADILAN PIDANA INDONESIA - Nur, Muhammad (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2012)
One of means to eradicate corruption is preventing corruptors to go abroad. Prevention is basically an instrumentof limiting of indivudual rights and therefore it is considered againts human rights. However, prevention conduetedby the corruption Eradication Commision on the corruptors is not considered as againts human rights since it ispart of restriction on human rights in the light of law enforcement. It does not also violate the presumption ofinnocence as part of criminal procedure. the authority of the Corruption Eradiction Commission is legitimateand in accordance with legal principle that state may have right to restrain the rights of citizens for the sake ofstate interests and society.